Naringenin suppresses NLRP3 inflammasome activation via the mRNA-208a signaling pathway in isoproterenol-induced myocardial infarction - Ayman Eldourghamy; Toka Hossam; Mohammed Abdalla Hussein; Amal Abdel-Aziz; Samir A. El-masry (Asian Pacific Journal of Tropical Biomedicine, 2023)
Objective: To investigate the cardioprotective effect of naringenin against isoproterenol (ISO)-induced cardiotoxicity in rats. Methods: Rats were divided into five groups: the normal group, the ISO group (85 mg/kg b.w.); the ISO+naringenin (50 mg/kg b.w.) group, the ISO+naringenin (100 mg/kg b.w.) group and the ISO+propranolol (10 mg/kg b.w.) group. Plasma creatine kinase-MB (CK-MB), cardiac troponin T, lactate dehydrogenase, brain natriuretic peptide (BNP), and IL-10, as well as cardiac transforming growth factor-β1 (TGF-β1), vascular endothelial growth factor (VEGF) and malondialdehyde (MDA) were examined. In addition, NLRP3 and mRNA-208a expressions were evaluated by RT-PCR analysis. Histopathological examination was also performed to assess cardiac damages. Results: Naringenin treatment significantly decreased plasma lactate dehydrogenase, CK-MB, cardiac troponin T, BNP, and IL-10, as well as cardiac TGF-β1, VEGF, and MDA while increasing p-Akt and superoxide dismutase in ISO-administered rats. It also reduced NLRP3 and mRNA-208a gene expression levels. Furthermore, naringenin improved ISO-induced cardiac damage. Conclusions: Naringenin attenuates myocardial dysfunction in ISO-treated rats by decreasing oxidative stress and increasing cardiac endogenous antioxidant system, which may be modulated partly by improvement of NLRP3 and mRNA-208a gene expression.